1998
DOI: 10.1042/bj3290073
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for altered sensitivity of the nitric oxide/cGMP signalling cascade in insulin-resistant skeletal muscle

Abstract: Nitric oxide activates guanylate cyclase to form cGMP, comprising a signalling system that is believed to be a distinct mechanism for increasing glucose transport and metabolism in skeletal muscle. The effects of a selective cGMP phosphodiesterase inhibitor, zaprinast, on basal glucose utilization was investigated in incubated rat soleus muscle preparations isolated from both insulin-sensitive (lean Zucker; Fa/?) and insulin-resistant (obese Zucker; fa/fa) rats. Zaprinast at 27 μM significantly increased cGMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 45 publications
5
59
0
Order By: Relevance
“…Although NO seems to be important for glucose uptake in individuals with type 2 diabetes, there is evidence in humans to suggest that individuals with type 2 diabetes have impaired resting NO-dependent vascular responses (48) and in animals that resting skeletal muscle NOS expression and activity are lower than in relevant control subjects (49,50). These results suggest that NOS protein and activity at rest may be reduced in humans with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although NO seems to be important for glucose uptake in individuals with type 2 diabetes, there is evidence in humans to suggest that individuals with type 2 diabetes have impaired resting NO-dependent vascular responses (48) and in animals that resting skeletal muscle NOS expression and activity are lower than in relevant control subjects (49,50). These results suggest that NOS protein and activity at rest may be reduced in humans with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 61%
“…It is likely that NO mediates its effects via stimulation of soluble guanylate cyclase and production of cGMP. Inhibition of cGMP breakdown with Zaprinast, a specific inhibitor of cGMP type 5 phosphodiesterase in incubated rat soleus muscle, raised skeletal muscle cGMP levels by ϳ90% and substantially increased glucose uptake (49). This finding, together with the known stimulatory effect of NO donors such as sodium nitroprusside on skeletal muscle glucose uptake (12,14), highlights the NO-glucose uptake mechanism as a potential therapeutic target in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 62%
“…Both muscle contraction [42] and SNP [18,42] increase cGMP formation. Furthermore pharmacological manipulation of both soluble guanylate cyclase and cGMP modulates the effect of SNP on glucose uptake [18,43].…”
Section: Signalling Pathwaysmentioning
confidence: 99%
“…In support of this hypothesis, recent studies have shown that NO synthase (NOS) is expressed in skeletal muscle (26) and that NO per se could influence muscle glucose metabolism in studies in animals and in vitro (27). In fact, NOS inhibition by Nmonomethyl-L-arginine inhibits glucose transport in incubated skeletal muscle preparations (28), and it has been shown that sodium nitroprusside, an NO donor, increases glucose transport both in the absence and presence of insulin in rat extensor digitorum longus muscle in vitro (29). Insulin-resistant obese Zucker fa/fa rats were found to have a defect in the metabolic pathway of NO, and the administration of Zaprinast, a selective cGMP phosphodiesterase inhibitor, increased both cGMP levels and glucose uptake in skeletal muscle (28).…”
Section: Euglycemic-hyperinsulinemic Clampmentioning
confidence: 99%